2015
DOI: 10.4103/0974-7796.152056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on International Prostate Symptom Score and prostate volume

Abstract: Aim:The aim of this study was to investigate the relationship between obesity and lower urinary tract symptoms and prostate volume in patients who underwent prostate biopsies.Materials and Methods:Between December 2008 and November 2009, transrectal ultrasound-guided prostate biopsy was performed on patients who had elevated prostate-specific antigen levels or abnormal digital rectal examination findings. A total of 211 patients were included in this study. Prostate volumes, International Prostate Symptom Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
2
17
0
5
Order By: Relevance
“…Obesity is strongly associated with prostate volume and pro-inflammatory factors released from visceral fat [ 2 23 24 ]. As a consequence, there is evidence linking obesity and incidence or progression of LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is strongly associated with prostate volume and pro-inflammatory factors released from visceral fat [ 2 23 24 ]. As a consequence, there is evidence linking obesity and incidence or progression of LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this may be that while LUTS occurrence and progression are related to aging, BMI and MAC are not consistent in their relationship with aging. On the contrary, some other studies have reported significant positive correlation [28] or negative correlation [29] between LUTS and BMI as well as other components of metabolic syndrome. These conflicting observations suggest that there may be no direct causal relationship between LUTS, BMI, MAC and other metabolic syndrome components.…”
Section: Discussionmentioning
confidence: 96%
“…Obesity and marked subepithelial fibrosis are the most significant findings of this study. Oberbach et al reported that weight loss had no impact on regression of the bladder fibrosis in their experimental study [ 24 ], but some advocated that a decrease in BMI caused relief for lower urinary tract symptoms [ 25 ].…”
Section: Discussionmentioning
confidence: 99%